THE CLINICAL COURSE OF COVID-19 PNEUMONIA - Dadabaeva Naila Akramovna; Mirahmedova Hilola Tukhtasinovna; Mirzaliyeva Anora Arginbaevna; Abdullaev Ulugbek Sayfullaevich (Western European Studies, 2025)
Plague and smallpox have been replaced by dangerous viral infections in the new century. The study of coronavirus allows to development of more effective methods of diagnostics, treatment, and vaccination, which contributes to public health.
Keywords: coronavirus; COVID-19 pneumonia